2019
DOI: 10.1038/s41380-019-0604-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Type-I interferon signaling adversely affects the microglia and the behavior of the offspring accompanied by increased sensitivity to stress

Abstract: Viral infection during pregnancy is often associated with neuropsychiatric conditions. In mice, exposure of pregnant dams to the viral mimetic poly(I:C), serves as a model that simulates such pathology in the offspring, through a process known as Maternal Immune Activation (MIA). To investigate the mechanism of such effect, we hypothesized that maternal upregulation of Type-I interferon (IFN-I), as part of the dam's antiviral response, might contribute to the damage imposed on the offspring. Using mRNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 116 publications
(168 reference statements)
6
48
3
Order By: Relevance
“…In contrast, the intracerebroventricular injection of rIFN-β increased the pro-inflammatory state of microglia cells and complement-dependent synapse elimination in the CNS of a mouse AD model, while blocking the type-I IFN receptor IFNAR1 diminished these effects [209]. The number of IBA1-, CD45-and CD68-positive microglia was also increased following the IFN-β treatment of GBM8-fluc-implanted athymic nude mice [210] and in the offspring of IFN-β-treated mice [211]. In line with these results, the microglial surface expression of the inflammation-associated Fc receptor and major histocompatibility complex class II (MHC-II) proteins was increased following the in vitro administration of IFN-β [212].…”
Section: Microgliamentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, the intracerebroventricular injection of rIFN-β increased the pro-inflammatory state of microglia cells and complement-dependent synapse elimination in the CNS of a mouse AD model, while blocking the type-I IFN receptor IFNAR1 diminished these effects [209]. The number of IBA1-, CD45-and CD68-positive microglia was also increased following the IFN-β treatment of GBM8-fluc-implanted athymic nude mice [210] and in the offspring of IFN-β-treated mice [211]. In line with these results, the microglial surface expression of the inflammation-associated Fc receptor and major histocompatibility complex class II (MHC-II) proteins was increased following the in vitro administration of IFN-β [212].…”
Section: Microgliamentioning
confidence: 98%
“…The levels of CCL5 and CCL2, two major chemo-attractants of peripheral immune cells, were increased in MG6-1 microglia cells, cultured in the presence of IFN-β and TNFα [ 215 ], and in IFN-β-treated primary mouse microglia cultures [ 202 ]. Moreover, IFN-β and IFN-α enhanced the expression levels of TNF, IL-6, IL-1β, IL-1α, CXCL10, CXCL9 and NO in (LPS-stimulated) primary rodent microglia cultures [ 209 , 212 , 213 , 216 , 217 , 218 ] and microglia isolated after the maternal separation of the offspring of immune-activated dams [ 211 ]. Furthermore, the two interferons downregulated the levels of superoxide anions and glutamate [ 216 ], both related to neurotoxicity, and the IFN-β treatment of the primary cultures of microglia stimulated with DNA or RNA upregulated the expression of the members of the Pyrin and HIN200 domain-containing proteins (PYHIN) family of DNA sensors [ 219 ], all again pointing to an IFN-mediated switch towards a more pro-inflammatory microglia milieu.…”
Section: Molecular Effects Of Fda-approved Ms Drugs On Cns Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toll-like receptor 3 (TLR3) activation or application of single cytokines such as IL-6 could for example be used to phenocopy (to some extent) MIA in vitro using a human model system. This could then be compared to data from rodent models, for example the effect on microglia transcriptional profile and chromatin state, which is known to be abnormal early in development following MIA (122,123). Such studies could be extended to examine how the inflammatory exposure might interact with specific genetic risk backgrounds, although this likely would be a complex undertaking.…”
Section: Haenseler Et Al (10)mentioning
confidence: 99%
“…Interestingly, a few reports have suggested that MIA alters gene expression in fetal microglia (Ben-Yehuda et al, 2020;Matcovitch-Natan et al, 2016;Mattei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%